Bioconversion of chitin to chitosan: purification and characterization of chitin deacetylase from Mucor rouxii. - Kafetzopoulos, D (1993)
Chitin deacetylase, the enzyme that catalyzes the hydrolysis of acetamido groups of N-acetylglucosamine in chitin, has been purified to homogeneity from mycelial extracts of the fungus Mucor rouxii and further characterized. The enzyme exhibits a low pI (approximately 3). Its apparent molecular mass was determined to be approximately 75 kDa by sodium dodecyl sulfate/polyacrylamide gel electrophoresis and approximately 80 kDa by size-exclusion chromatography, suggesting that the enzyme exists as a monomer. Carbohydrate analysis of purified chitin deacetylase revealed that the enzyme is a high-mannose glycoprotein and that its carbohydrate content is approximately 30% by weight. Chitin deacetylase is active on several chitinous substrates and chitin derivatives. The enzyme requires at least four N-acetylglucosamine residues (chitotetraose) for catalysis, and it is inhibited by carboxylic acids, particularly acetic acid. When glycol chitin (a water-soluble chitin derivative) was used as substrate, the optimum temperature for enzyme activity was determined to be approximately 50 degrees C and the optimum pH was approximately 4.5.